Pulse coupled oscillator synchronization for low power UWB wireless transceivers - Wang, X.Y.; Apsel, A.B. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
Achieving robust synchronization in low power UWB systems remains a dominant obstacle in the design of these systems. In this paper, we propose using the pulse coupled oscillator (PCO) phenomenon with system feedback as an alternative scheme to conventional master-slave synchronization using power hungry PLL or DLL circuits. Sensor network nodes implementing the PCO state function are mathematically guaranteed to converge towards phase lock, with no need for a PLL, off chip crystal, or continuously operating low noise amplifier. To date, we know of no circuit-level implementation of a PCO based wireless transceiver. We also demonstrate synchronization of a switchable integrated transceiver front-end in the IBM CMOS7RF process, a key first step in design of short-range communications for microwatt power levels.